2015
DOI: 10.1111/amet.12157
|View full text |Cite
|
Sign up to set email alerts
|

State, corruption, postcoloniality: A conversation with Akhil Gupta on the 20th anniversary of “Blurred Boundaries”

Abstract: It went on to become one of the most important and influential articles of recent decades. We talked with Akhil Gupta about how the argument put forward in "Blurred Boundaries" came to be. Our conversation touched on the background of the article and the difficulties in getting it published; the relationship of the article to postcolonial scholarship, subaltern studies, feminist studies, and the then emerging literature on globalization; its relationship with other theorists of the state through themes such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…There is evidence that formula milk companies ignore the laws and continue marketing their products inappropriately [42]. The literature from Pakistan and India shows that corruption within medical settings restricts government services [26,43]. While drawing upon the anthropology of the state along with the perspective of structural violence, Gupta found that funds hardly reach their anticipated beneficiaries but mostly reach people with political acquaintances, cultural capital, and financial influence [44].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that formula milk companies ignore the laws and continue marketing their products inappropriately [42]. The literature from Pakistan and India shows that corruption within medical settings restricts government services [26,43]. While drawing upon the anthropology of the state along with the perspective of structural violence, Gupta found that funds hardly reach their anticipated beneficiaries but mostly reach people with political acquaintances, cultural capital, and financial influence [44].…”
Section: Discussionmentioning
confidence: 99%
“…Enquanto nos primeiros a localização estrutural dos diálogos contempla as regiões centrais -os centros urbanos de capital, a alta política, a administração e a educação -os segundos delineiam as naturezas multicamadas e pluricêntricas do Estado, distinguindo-se entre um ente central e suas distintas representações burocráticas locais. As construções do Estado irão variar de acordo com a forma como os diferentes atores estão posicionados socialmente (Gupta, 1995), mesmo com todos os mecanismos para representá-lo como um ator coerente e unificado (Gupta, Nugent, & Sreenath, 2015), como idealizado na visão eurocentrista.…”
Section: Corrupção Transnacionalunclassified
“…The ‘sites of entitlement’ approach seems particularly well suited to examining differential access to urban services in India, and other countries where citizen rights do not necessarily bear close relation to entitlements. Van Dijk (2011a) argues that the personalized nature of Indian bureaucracy (see also Gupta et al ., ), coupled with the state's low infrastructural power, results in ‘gaps between both the formal–legal channels of entitlement actualization (and informal channels) and differently positioned places or collectivities’ (van Dijk, : 307). Similar conditions can be found in other postcolonial cities where the demand for government services outstrips supply, increasing the likelihood of ‘informal regimes of citizenship’ (Berenschot and van Klinken, ), clientelism, and other forms of patronage.…”
Section: Citizen Entitlementsmentioning
confidence: 99%